INTERACTION OF K AND B IN THE INTENSITY OF COFFEE RUST IN NUTRIENT SOLUTION - Vasco, Gabriel Brandão; Pozza, Edson Ampélio; Silva, Marília Goulart da; Alexandre Pozza, Adélia Aziz; Chaves, Eugênio (Coffee Science - ISSN 1984-3909, 2018)
This study aimed at assessing the interaction of potassium (K) and boron (B) in the coffee rust intensity in a nutrient solution. The experiment which was performed in a greenhouse was set up in the randomized complete block design (DBC) with four replicates. The experimental unit involved a single vase with two Catuaí Vermelho (IAC 144) cultivars. The treatments included five doses of boron (0.05, 0.50, 1, 2 and 4 mg L-1) and five of potassium (4.0, 5.0, 6.0, 7.0 and 8.0 mmol L-1), totaling to 25 treatments in a factorial variance analysis. All the coffee seedling leaves were inoculated with Hemileia vastatrix. For the next 24 hours, the vases were covered with a black plastic bag, and left in the greenhouse to ensure favorable conditions for the fungal infection. A significant interaction was observed between the potassium (K) and boron (B) nutrients in coffee rust intensity. As the boron dose increased from 0.05 to 2.0 mg L-1, the coffee rust intensity was observed to rise. From the 0.50 mg L-1 dose of B a drastic drop in the dry plant mass was observed, which reached zero index at the highest boron dose due to phytotoxicity.